A contractarian view on homann's ethical approach: The vision of "new ordoliberalism" - Clem Davies; Marcel Franke; Lida Kuang; Karl Justus Bernhard Neumärker (University of Freiburg, Institute for Economic Research, Department of Economic Policy and Constitutional Economic Theory, 2022)
Homann's method is a sophisticated theoretical model. As a result, it contains a normative foundation upon which Homann bases his endeavor, as well as numerous conclusions following his positive analysis. We propose extensions to both the normative and positive aspects of Homann's theory in this article. On a normative basis, we recommend taking into account our approach of New Ordoliberalism. In addition to the prisoner's dilemma, we consider the moral dilemma of the hawk-dove game on a positive footing. Additionally, we also present an experimental design. – – Die Methode Homanns ist ein ausgefeiltes theoretisches Modell. Es enthält sowohl eine normative Grundlage, auf der Homann sein Unterfangen aufbaut, als auch zahlreiche Schlussfolgerungen, die sich aus seiner positiven Analyse ergeben. In diesem Artikel entwickeln wir Erweiterungen sowohl für die normativen als auch für die positiven Aspekte von Homanns Theorie. Zum Ausbau der normativen Dimension empfehlen wir unseren Ansatz des Neuen Ordoliberalismus zu berücksichtigen. In positiver Hinsicht betrachten wir das moralische Dilemma der Gesellschaft neben der Rekonstruktion im Gefangenendilemma auch im Falke-Taube-Spiel. Weiterhin stellen wir einen Versuchsaufbau hierzu vor.
Keywords: 330; constitutional economics; game theory; New Ordoliberalism; social contract experiment; strategy-proofness; renegotiation-proofness; Ordnungsökonomie; Spieltheorie; Neuer Ordoliberalismus; Sozialvertragsexperiment; Manipulationssicherheit; Nachverhandlungsstabilität